Karakteristik Fisikokimia dan Aktivitas Antioksidan Minuman Fungsional Wedang Pokak Instan Khas Madura - Supriyanto Supriyanto; Ilham D Apriyan; Dian F Asfan (Universitas Pattimura, 2025)
Wedang pokak is a traditional spiced beverage originating from East Java, particularly Madura. It is prepared using ginger, lemongrass, cloves, cinnamon, lime leaves, fragrant pandan leaves, and palm sugar, which are boiled, filtered, and served. Due to its composition, Wedang pokak has the potential to be developed as a functional beverage rooted in local wisdom. One approach to enhance its accessibility and shelf life is by processing it in an instant form. This research aimed to evaluate the effect of the proportion of coating materials (maltodextrin: gum arabic) and the spray dryer inlet temperature on the physicochemical properties, antioxidant activity, and sensory characteristics of instant wedang pokak. A completely randomized design was employed, and two factors were used: coating material ratios and spray drying temperature. The first factor icluded three formulations: P1 (maltodextrin 70 : gum arabic 30), P2 (maltodextrin 50 : gum arabic 50), and P3 (maltodextrin 30 : gum arabic 70), and the second factor comprised two inlet temperature S1 (160°C) and S2 (180°C). The results showed that both the coating ratio and drying temperature had a significant effect (P < 0.05) on the physicochemical and sensory characteristics of instant wedang pokak. The best formulation was P3S1 (maltodextrin 30 : gum arabic 70, temperature 160°C), which exhibited a dissolution time of 11.04 minutes, moisture content of 6.83%, pH of 7, and antioxidant activity of 94.67% RSA. This sample also received favorable sensory scores, with mean values for color 3.44 (like), taste 3.24 (like), aroma 3.28 (like), and overall accepatability3.44 (like).